Integrasi Media Sosial dalam Literasi Dakwah Digital Pelajar Sekolah Menengah - Sitto Rahmana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Social media has transformed how adolescents access information, interact, and produce digital content. This transformation creates both opportunities and risks, particularly related to misinformation, low digital literacy, and weak communication ethics. This community service program aims to improve secondary school students’ ability to produce creative, moderate, and responsible digital da’wah content through social media. The program applied an Asset-Based Community Development (ABCD) approach with a participatory model. It involved 28 junior high school students through asset mapping, training sessions, content production workshops, mentoring, and evaluation. Evaluation instruments included pre-test and post-test assessments, skill rubrics, and participant response questionnaires. The results show an increase in the average knowledge score from 78 to 86. Participants successfully produced three digital da’wah contents, including short videos, posters, and infographics, of which three were approved for publication after content curation. Participant responses were categorized as good with an average score of 85 percent, indicating improved understanding of information literacy, digital da’wah ethics, and media production skills. In conclusion, the program is effective in enhancing students’ competence as producers of digital da’wah content. Sustainability requires continuous support from schools, teachers, and student organizations to build a long-term digital da’wah ecosystem.